Review Article: Is Wnt Signaling an Attractive Target for the Treatment of Osteoarthritis? - Lories, Rik J. (Rheumatol Ther, 2020)
Osteoarthritis is the most common chronic joint disease affecting millions of people worldwide and a leading cause of pain and disability. Increasing incidence of obesity and aging of the population are two factors that suggest that the impact of osteoarthritis will further increase at the society level. Currently, there are no drugs available that can manage both structural damage to the joint or the associated pain. Increasing evidence supports the view that the Wnt signaling pathway plays an important role in this disease. The current concept, based on genetic and functional studies, indicates that tight regulation of Wnt signaling in cartilage is essential to keep the joint healthy. In this review, we discuss how this concept has evolved, provide insights into the regulation of Wnt signaling, in particular by Wnt modulators such as frizzled-related protein and DOT1-like histone lysine methyltransferase, and summarize preclinical evidence and molecular mechanisms of lorecivivint, the first Wnt antagonist in clinical development for osteoarthritis.